Micron to nanometre‐scale pore characterisation of the early oil window Vaca Muerta Formation, Neuquén Basin, Argentina - Eider Hernandez‐Bilbao; J. Rick Sarg; Stephen A. Sonnenberg (The Depositional Record, 2021)
Abstract This paper characterises the pore types and their distribution in the Vaca Muerta Formation, Neuquén Basin, Argentina. This formation is now being studied and targeted as reservoir rock, and it is therefore considered an unconventional resource play. There is significant need for a porosity description as part of the unconventional reservoir characterisation. Mineral compositions, grain assemblages, morphology, organic content and distribution, and micron to nanometre‐scale pore types are studied through scanning electron microscopy. Petrographic observations depict the complex response of pores to chemical and mechanical processes, where both destruction of primary porosity and generation of secondary pores are common. Compaction, cementation and infill of migrated organic matter destroy primary porosity whereas dissolution and secondary organic matter generated through maturation create secondary pores. Lamina sets with major detrital components can help identify intervals with higher interparticle and intraparticle porosity. Interparticle and intraparticle porosity are ubiquitous throughout the samples. Interparticle pores are common around rigid detrital grains, like quartz and feldspar, and within detrital clay platelets. Porosity within authigenic clay cements is included, as framework porosity and samples may contain up to a maximum of 30 wt% clay. Partial grain dissolution of coccoliths, feldspars and calcite grains resulted in available intraparticle pore space. Organopores are the least abundant pore types at this location. Organopores were described within migrated organic matter. Although the kerogen type (Type II) and the vitrinite reflectance are optimum for hydrocarbon generation (ca 0.80% Ro) in the Vaca Muerta Formation at the study area, development of organopores is not common. The Vaca Muerta Formation has experienced insufficient thermal maturation (early oil window) and has not yet reached peak oil.